2017
DOI: 10.18203/2320-1770.ijrcog20172895
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-histopahological patterns of benign gynecological lesions at a tertiary hospital in Eastern Nigeria: a 5 year review

Abstract: Background: Gynecological lesions are a common reason for women to seek specialist care. Even benign lesions manifest with a wide variety of clinical features. This study set out to analyze the prevalence of histopathologically evaluated benign lesions of the genital tract and their diverse clinical presentations within a tertiary healthcare institution.Methods: This was a retrospective study of 265 cases of gynecological specimens sent for histopathology at department of morbid anatomy, relevant clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The majority of the participants showed a correct knowledge of the predisposing factors, which included stress, obesity, hereditary, early menarche, caffeine, smoking and hormones. This is consistent with the studies of (59, 60, 61). A few participants indicated that uterine fibroids are caused by having multiple partners, although a study conducted by Azzahra, Gondodiputro (62) proved that there is no association between this factor and uterine fibroids.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the participants showed a correct knowledge of the predisposing factors, which included stress, obesity, hereditary, early menarche, caffeine, smoking and hormones. This is consistent with the studies of (59, 60, 61). A few participants indicated that uterine fibroids are caused by having multiple partners, although a study conducted by Azzahra, Gondodiputro (62) proved that there is no association between this factor and uterine fibroids.…”
Section: Discussionsupporting
confidence: 93%